2016
DOI: 10.1073/pnas.1606742113
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-resident E3 ubiquitin ligase Hrd1 controls B-cell immunity through degradation of the death receptor CD95/Fas

Abstract: Humoral immunity involves multiple checkpoints during B-cell development, maturation, and activation. The cell death receptor CD95/Fas-mediated apoptosis plays a critical role in eliminating the unwanted activation of B cells by self-reactive antigens and in maintaining B-cell homeostasis through activation-induced B-cell death (AICD). The molecular mechanisms controlling AICD remain largely undefined. Herein, we show that the E3 ubiquitin ligase Hrd1 protected B cells from activation-induced cell death by deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
(41 reference statements)
2
33
0
Order By: Relevance
“…HRD1 floxed mice were used as previously described (Kong et al , ; Xu et al , ; Yang et al , ). Albumin‐Cre (catalogue no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD1 floxed mice were used as previously described (Kong et al , ; Xu et al , ; Yang et al , ). Albumin‐Cre (catalogue no.…”
Section: Methodsmentioning
confidence: 99%
“…The IRE1α downstream transcription factor Xbp‐1 has been shown to regulate HRD1 mRNA transcription, providing an interesting feedback loop for HRD1‐IRE1α during ER stress response (Gao et al , ). We recently found that HRD1 is involved in immune regulation in dendritic cell antigen presentation, as well as in the activation of both T and B lymphocytes (Kong et al , ; Xu et al , ; Yang et al , ). However, it is not clear whether HRD1 is regulated upon metabolic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings, it is likely that the reduced mature B cell number in Hrd1 KO bone marrow is due to defective pre-BCR down-regulation in the pre-B cell population, which results in reduced mature BCR expression and signaling that is required for mature B cell survival. In fact, we have recently discovered that Hrd1 regulates activation-induced B cell death through targeting the death receptor Fas (36). Therefore, Hrd1 appears to be critical to regulate B cell functions at multiple distinct stages.…”
Section: Hrd1 Governs B Cell Developmentmentioning
confidence: 99%
“…Subsequent characterization of cell type‐specific Sel1L‐knockout (Ji et al , ; Sha et al , ; Shi et al , ; Sun et al , , , ) and Hrd1‐knockout (Fujita et al , ; Kong et al , ; Wu et al , ; Xu et al , ; Yang et al , ) mouse models, including gene deletion in adipocytes, immune cells, enterocytes, and various neurons, has revealed the significance of Sel1L‐Hrd1 ERAD in a cell type‐ and substrate‐specific manner in vivo (Qi et al , ). For example, mice with Sel1L deficiency in adipocytes exhibit lipodystrophy and postprandial hyperlipidemia due to the ER retention of lipoprotein lipase (LPL) (Sha et al , ).…”
Section: Introductionmentioning
confidence: 99%